Magnetic field modulation of the delayed fluorescence yield in the photoionization reaction of N, N, N', N'-tetramethyl-p-phenylenediamine in water - Sameh Saad Ali; Günter Grampp; Stephan Landgraf; Michael Sacher (International Journal of Photoenergy, 1999)
External magnetic field effects on the recombination fluorescence (MARY effect) in the photoionization reaction of N,N,N′,N′-Tetramethyl-p-phenylenediamine (TMPPD) in water and DMSO/water mixture are studied. Relatively large magnetic field effects (MFE), ∼ 2–4%, on the fluorescence yield are observed in the extremely polar water solvent under magnetic fields as small as 3 mT. Such MFE is hardly expected in water due to instability and very fast escape of the solvated electron from the solvent cage. Enhancement in the signal-to-noise ratio and superior time resolution characterizing the technique of field modulation allowed the detection of a very short lived radical ion pair (about 1 ns). The observed MARY spectra illustrate that the singlet radical ion pair is more reactive than the triplet one.